Post-metallization annealing and photolithography effects in p-type Ge/Al2O3/Al MOS structures. (1st April 2022) - Ioannou-Sougleridis, V.; Alafakis, S.; Pécz, B.; Velessiotis, D.; Vouroutzis, N. Z.; Ladas, S.; Barozzi, M.; Pepponi, G.; Skarlatos, D.
Abstract : In this work, the combined effect of negative tone photolithography and post-metallization annealing (PMA) on the electrical behavior of Al/Al2 O3 /p-Ge MOS structures are investigated. During photoresist development, the exposed upper part of the Al2 O3 film weakens due to the reaction with the developer. Subsequent processes of Al deposition and PMA at 350 °C result in alumina thickness reduction. The gate electrode formation seems to involve at least three processes: (a) germanium substrate out-diffusion and accumulation at the top of the alumina layer that takes place during the alumina deposition, (b) alumina destabilization, and (c) germanium diffusion into the deposited Al metal and Al diffusion into the alumina. The overall effect is the reduction of the alumina thickness due to its partial consumption. It is shown that the germanium diffusion depends on the annealing duration, and not on the annealing ambient (inert or forming gas). Although PMA passivates interface traps near the valence band edge, the insulating properties of the stacks are degraded. This degradation appears as a low-level ac loss, attributed to a hopping current that flows through the Al2 O3 layer. The results are discussed and compared to recently reported on Pt/Al2 O3 /p-Ge structures formed and treated under the same conditions.